Meningkatkan Minat Baca Masyarakat Melalui Gerakan Literasi di Desa - Rahmawati, Indri; Risnayanti, Ai; Nurcahyani, Dona Siti; Nurlaela, Neng Siti; Misbahudin, Misbahudin (Saneskara: Journal of Social Studies, 2024)
This research aims to evaluate the effectiveness and impact of a literacy program implemented in Citanglar Village, Surade District, Sukabumi Regency, with a focus on socializing activities to increase the local community's interest in reading. This literacy program is designed to provide a holistic and sustainable approach to increasing accessibility, reading skills, and literacy appreciation among village residents. This research uses a participatory action research (PAR) approach, which involves actively gathering various information and then taking action to overcome the identified problems. This involvement includes contributing to the development and implementation of actions based on research findings. This research was carried out by implementing a literacy program in four places, including SDN Sukaresmi, Posko KKM, Paud At-Taqwa, and MTs As-Shobariyyah, reaping positive responses and a good influence on the community in seeing the urgency of literacy.